Systemic Immune-Inflammation Index and Long-Term Mortality in Patients with Stroke-Associated Pneumonia - Xie M; Yuan K; Zhu X; Chen J; Zhang X; Xie Y; Wu M; Wang Z; Liu R; Liu X (Dove Medical Press, 2023)
Mengdi Xie,1,* Kang Yuan,2,* Xinyi Zhu,2,* Jingjing Chen,3 Xiaohao Zhang,4 Yi Xie,2 Min Wu,1 Zhaojun Wang,2 Rui Liu,2 Xinfeng Liu1,2,5 1Department of Neurology, Jinling Hospital, Nanjing Medical University, Nanjing, People's Republic of China; 2Department of Neurology, Affiliated Jinling Hospital, Medical School of Nanjing University, Nanjing, People's Republic of China; 3Department of Neurology, Changhai Hospital, Navy Medical University, Shanghai, People's Republic of China; 4Department of Neurology, Nanjing First Hospital, Nanjing Medical University, Nanjing, People's Republic of China; 5Stroke Center & Department of Neurology, Division of Life Sciences and Medicine, The First Affiliated Hospital of USTC, University of Science and Technology of China, Hefei, Anhui, People's Republic of China*These authors contributed equally to this workCorrespondence: Xinfeng Liu, Department of Neurology, Jinling Hospital, Nanjing Medical University, No. 305 East Zhongshan Road, Nanjing, Jiangsu Province, 210000, People's Republic of China, Tel +86 2584801861, Fax +86 2584805169, Email xfliu2@vip.163.com Rui Liu, Department of Neurology, Affiliated Jinling Hospital, Medical School of Nanjing University, No. 305 East Zhongshan Road, Nanjing, 210000, Jiangsu Province, People's Republic of China, Tel +86 2584801861, Fax +86 2584805169, Email liurui8616@163.comBackground: Systemic immune inflammation has been investigated as a prognostic marker of different diseases. This study is designed to assess the association of systemic immune-inflammation index (SII) with long-term mortality of stroke-associated pneumonia (SAP) patients.Methods: Patients aged ≥ 18 years with SAP were selected from the Nanjing Stroke Registry Program in China. We retrospectively evaluated systemic immune-inflammation response with SII and pneumonia severity with the pneumonia severity index and the confusion, uremia, elevated respiratory rate, hypotension, and aged 65 years or older score. To explore the correlation between SII and mortality in SAP patients, multivariable Cox regressions and competing risk regressions were conducted. Mediation analysis was also performed to assess the role of pneumonia severity.Results: Among 611 patients in the SAP population, death occurred in 164 patients (26.8%) during the median follow-up of 3.0 (1.2- 4.6) years. In multivariate analysis, higher SII scores could predict increased mortality in patients with SAP (adjusted hazard ratio 2.061; 95% confidence interval, 1.256- 3.383; P = 0.004), and the association was mediated by pneumonia severity. Moreover, adding SII to traditional models improved their predictive ability for mortality.Conclusion: Our study displayed that SII was characterized in SAP patients with different prognoses. Elevated SII scores increased the risk of mortality. Further research is required for the clinical practice of the index among SAP patients.Keywords: systemic immune-inflammation index, stroke-associated pneumonia, mortality, China